2013
DOI: 10.3109/13880209.2013.836544
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis and tissue distribution of andrographolide in rat by a validated LC-MS/MS method

Abstract: Context: Andrographis paniculata (Burm.f.) Nees (Acanthaceae) is widely used in tribal medicine in India and some other countries for multiple clinical applications. It contains andrographolide (AG) (diterpenoid lactone), a major phytomarker which probably accounts for its medicinal properties.Objective: This study investigates the site-specific distribution of AG in different tissues of rats and its pharmacokinetic parameter evaluation by using a validated liquid chromatography tandem mass spectrometry (LC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 14 publications
5
45
1
Order By: Relevance
“…Interestingly, there was an unexpected finding that double peaks appeared in both plasma concentration-time curves, which is not consistent with previous reports (Bera et al, 2014;Xu et al, 2009;Zhang and Fan, 2012;Zhao et al, 2013). This may be attributed to the fact that the metabolism of ADG is very different among different species.…”
Section: Bioavailability Studycontrasting
confidence: 65%
“…Interestingly, there was an unexpected finding that double peaks appeared in both plasma concentration-time curves, which is not consistent with previous reports (Bera et al, 2014;Xu et al, 2009;Zhang and Fan, 2012;Zhao et al, 2013). This may be attributed to the fact that the metabolism of ADG is very different among different species.…”
Section: Bioavailability Studycontrasting
confidence: 65%
“…The molecular formula of andrographolide is C 20 H 30 O 5 and it is one of the active components of A. paniculata extract, comprising up to 1.84% of the extract (10,11). Andrographolide has been produced as a raw material with antipyretic and analgesic effects (12).…”
Section: Introductionmentioning
confidence: 99%
“…Mean apparent volume of distribution (Vd area : 6.9 ± 0.38 L/kg) of andrographolide following intramuscular administration in rats was found higher than reported following oral administration (0.04 ± 0.005 and 0.06 ± 0.1) of Andrographis paniculata extract (20 and 200mg/kg) in rats respectively (Pannossian et al, 2000). This finding was supported by higher value of AUC (13.7 ± 0.47 g.h/mL) in comparison with findings reported following oral administration of andrographolide (30mg/kg) and ethanolic extract of Andrographis paniculata (20 and 200 mg/kg) in rats respectively (Bera et al, 2014;Pannossian et al, 2000). Moreover, low plasma protein (55%) binding efficiency of drug (Dey et al, 2013) can also contribute high distribution of andrographolide in rats.…”
Section: Treatment Groupmentioning
confidence: 31%
“…The mean absorption half-life (t ÂœKa : 0.60 ± 0.07 h)of andrographolidein rats following single dose intramuscular administration in the present study was in accordance to absorption half-life (0.69 ± 0.3 h) reported following oral administration of ethanolic extract of Andrographis paniculata (20 mg/kg) in rats (Pannossian et al, 2000). The elimination half-life (t 1/2ÎČ : 1.33 ± 0.10 h) of andrographolide in rats following single dose intramuscular administration in present study was found lower than elimination half-life (2.45 h, 3.1 ± 0.2 h and 2.5 ± 0.1 h;) reported following oral administration of andrographolide (30mg/kg) and ethanolic extract of Andrographis paniculata (20 and 200 mg/kg) in rats respectively (Bera et al, 2014;Pannossian et al, 2000). Mean apparent volume of distribution (Vd area : 6.9 ± 0.38 L/kg) of andrographolide following intramuscular administration in rats was found higher than reported following oral administration (0.04 ± 0.005 and 0.06 ± 0.1) of Andrographis paniculata extract (20 and 200mg/kg) in rats respectively (Pannossian et al, 2000).…”
Section: Treatment Groupmentioning
confidence: 43%
See 1 more Smart Citation